The inhibition of M-MLV and HIV-1 reverse transcriptase by polyphenols extracted from the resurrection plant Myrothamnus flabellifolia (Welw.) - Kamng'ona, Arox Wadson (Department of Molecular and Cell Biology, 2014)
Includes abstract.